Ecosystem health of a Mediterranean semi-enclosed embayment (Amvrakikos Gulf, Greece): Assessing changes using a modeling approach. (15th June 2016) - Piroddi, Chiara; Moutopoulos, Dimitrios K.; Gonzalvo, Joan; Libralato, Simone
Abstract: Marine and coastal ecosystems are important for human wellbeing in multiple ways and yet they are subject to increasing anthropogenic stressors which pose serious threats to their health status. In this context, we used an ecosystem modeling approach to assess and quantify the health status of a semi-enclosed embayment of the Mediterranean Sea, the Amvrakikos Gulf (surface: 405 km 2 ; maximum depth: 60 m) (Ionian Sea). In particular, we built a food web model of the Gulf ecosystem for the 1980 and we fit it to time series from 1980 to 2013. The aim of the study was to: (1) investigate dynamics of marine resources in the last three decades considering the effect of changes in rivers run off, development of fish farming and dynamics of fisheries as the major anthropogenic drivers affecting the system; (2) assess structural and functional changes of the Gulf, using model derived indicators obtained from temporal simulations. Results indicated that the strongest drivers in the Amvrakikos food web were changes in nutrients and organic matter mostly from the loads of two local rivers. Trends in ecological indicators, which explained changes in the structure of the Gulf, highlighted a degradation of the demersal compartments of the food web and a relative stability of the pelagic ones mainly due to high eutrophication levels. By including several ecosystem drivers into the model, the present study is intended as a tool for assessing Amvrakikos ecosystem health and for developing future management policies in the Gulf. Highlights: We built a food web model for the Amvrakikos Gulf ecosystem. Nutrients and organic matter mostly from the loads of local rivers were the major drivers. Trends in ecological indicators showed degradation of the demersal compartments of the food web and a relative stability of the pelagic ones.